Risk Attributes, Influencing the Time and Cost Overrun in Joint Venture Construction Projects of Pakistan - Akhund, M. A.; Khoso, A. R.; Pathan, A. A.; Imad, H. U.; Siddiqui, F. (Engineering, Technology & Applied Science Research, 2018)
Business collaborations formed by construction contractors to enhance their abilities and effectiveness in large construction projects are known as construction joint ventures (CJVs). It is widely used as a way of merging assets, capitals, funds, resources and expertise of different organizations. It helps business to grow faster, increase efficiency and generate greater profits without borrowing money. Though it is useful and beneficent for the vendors, it may contain several types of risk. It is both beneficial and stimulating due to differing technical skills, economic and political atmospheres, and cultural and legal backgrounds. Recent development and modernization in Pakistan have led it towards a new construction phase, which involves national and multinational joint venture projects. Global and local CJVs have become gradually prevalent to produce mega construction projects. Current research aims to investigate and to identify the communal, ecological, political, legal, economic and other external risks associated with CJV projects in Pakistan. The study was carried out by literature review and a few national and international guidelines. Interviews were conducted with relevant professionals, experts, and owners of the organizations working on CJV projects. Data was collected in the form of a questionnaire from relevant professionals. The descriptive analysis was performed through SPSS using average index (A.I) technique. This study is helpful for the Government of Pakistan, public and private construction firms working under JV to reduce the emerging risks of construction projects.